Analisis Indeks Morfometrik Otolith asteriscus Ikan swanggi (Priacanthus tayenus Ricardson, 1846) dari Perairan Selat Makassar - Kantun, Wayan; Sapa, Sri Ainun; Wulandari, Sri (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2024)
Purple-spotted bigeye is one of the aquatic resources which in the ecosystem functions to support the trophic level system in the food web in nature. This fish is the prey of predatory fish, so one way to prove the role of purple-spotted bigeye at the trophic level is to identify the microstructural organs located on the otolith. In this regard, this study aims to analyze the morphometric index and otolith shape index of the asteriscus type. This research is a type of quantitative research with a survey method. Sampling was carried out at fish landing sites in Paotere Makassar, Maros and Macini Baji Pangkep. The fish sampled were caught in the waters of the Makassar Strait. The research was conducted from April to June 2024. The number of samples was 92 purple-spotted bigeye with 92 pairs of asteriscus otoliths. Morphometric index calculations use small, medium and large sized fish. Meanwhile, the shape index calculation uses six descriptors which include from factor (FF), roundness (RO), circularity or compactness (C), rectangle (Rt), ellipticity (E), and aspect ratio (AR). The results of the research show that morphometrically the types of otoliths on both the right and left sides are relatively the same, the asteriscus otolith has a shape that tends to be oval, elongated, but has a regular surface shape.